Work-family conflict and cyberloafing: the mediating role of work stress - Aqsa Kusumawati; Rosaly Franksiska (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2018)
This study was conducted to analyze the effect of work-family conflict on work stress. Furthermore, we also examine the mediating role of work stress on the relatioship between work-family conflict on cyberloafing. Results of path analysis on 133 respondents form PT. AIC, Semarang, Indonesia shows that work-family conflict positively affects work stress. This research also indicated that work stress did not act as an intervening variable because the respondents had other stress coping mechanism than cyberloafing.